2017
DOI: 10.1007/s12035-017-0734-9
|View full text |Cite
|
Sign up to set email alerts
|

The Retina of Osteopontin deficient Mice in Aging

Abstract: Osteopontin (OPN) is a secreted glycosylated phosphoprotein that influences cell survival, inflammation, migration, and homeostasis after injury. As the role of OPN in the retina remains unclear, this study issue was addressed by aiming to study how the absence of OPN in knock-out mice affects the retina and the influence of age on these effects. The study focused on retinal ganglion cells (RGCs) and glial cells (astrocytes, Müller cells, and resident microglia) in 3- and 20-month-old mice. The number of RGCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 64 publications
2
19
1
Order By: Relevance
“…Our results indicated that there was a correlation between αvβ3 and OPN, and a correlation between αvβ3 and SAβ-gal, and a correlation between OPN and SAβ-gal also presence. These were in line with the former studies [29][30][31].Due to the ligand-receptor relationship between OPN and αvβ3, we infer that elevated OPN through the αvβ3 integrin affect the SAβ-gal expression and in uence the cellular senescence.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicated that there was a correlation between αvβ3 and OPN, and a correlation between αvβ3 and SAβ-gal, and a correlation between OPN and SAβ-gal also presence. These were in line with the former studies [29][30][31].Due to the ligand-receptor relationship between OPN and αvβ3, we infer that elevated OPN through the αvβ3 integrin affect the SAβ-gal expression and in uence the cellular senescence.…”
Section: Discussionsupporting
confidence: 92%
“…Ascorbic acid-mediated increase in OPN in the cerebellum are linked with the positive effects of OPN in other studies which reported OPN-induced promotion of survival, proliferation, migration of neural stem cells and proliferation, and differentiation of glial cells into oligodendrocytes [15,39]. Additionally, OPN is required for normal retinal development, and OPN deficiency induces premature aging effects in the retina [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the role of OPN in cellular migration, recent studies have shown that astrocyte polarization is linked to the integrin subunit and that depletion of hematogenous OPN resulted in the defective polarization of reactive astrocytes in a photothrombic stroke model [14, 59]. Furthermore, OPN deficient mice exhibited attenuation of reactive astrogliosis after stab wound injury [27], while the absence of OPN in the retina displayed a deficit in astrocyte coverage and linear extension and process branching indicative of premature aging [28]. In this regard, OPN’s overlapping distribution and often direct contact with astrocytes at days 7–14 after the 3-NP injury indicate a probable direct interaction of OPN protein with scar-forming astroglia, possibly involving the modulation of process elongation and polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have shown that macrophage-secreted OPN induces the polarization of reactive astrocytes after stroke [14] and that OPN is essential for astrocyte activation in an injured mouse brain, as well as in the primary culture of astrocytes [27]. In addition, OPN is necessary for the cell adhesion, migration, and survival of retinal astrocytes [28] and regulates metabolic activity in cultured optic nerve head astrocytes [29]. Thus, OPN plays a functional role not only in microglia/macrophages, but also in the astroglial reaction elicited by CNS insults.…”
Section: Introductionmentioning
confidence: 99%